FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KARIES GIGI PADA REMAJA DI KLINIK GIGI CHEESE BANDAR LAMPUNG TAHUN 2022 - Yesica Putri Arum; Dwi Yulia Maritasari; Budi Antoro (Jurnal Kesehatan Gigi (Dental Health Journal), 2023)
Dental caries can cause localized destruction of hard tissue in specific area of tooth decay in adolescents. According to the result of patient visit data in Cheese Dental Clinic Bandar Lampung on 2021 shows that 48% adolescetns have dental caries. The aims of this study is to know the factors related to dental caries against adolescents in Cheese Dental Clinic Bandar Lampung in 2022. This research is quantitative analytic observational by cross sectional approach. The sample are 60 adolescent patients aged 14-20 in Cheese Dental Clinic that taken by purposive sampling technique. DMF-T sheet is the instrument to measure the dental caries by adolescent patient direct inspection and self fulfillment questionnaire is used to findout knowledge variable, attitude, behavior and frequency of cariogenic food consumption. The data analysis uses chi-square test.. The result shows that the number of dental caries in middle category as many as 44 (73.3%) adolescent, whereas the low category consist of 16 (26.7%) adolescent. There is significant correlation between oral health knowledge (p-value=0.028, OR=4.444), oral health maintenance attitude (p-value=0.001, OR=9.000), oral health maintenance behavior (p-value=0.002, OR=8.143) and frequency of cariogenic food consumption (p-value=0.003, OR=7.500) in adolescent  dental caries incident. Educating about oral health is preferable by utilizing digital media in whatsapp story and educational video in waiting room television and providing leaflet about the need of chek-up periodically every once in 6 months